2005
DOI: 10.1111/j.1469-0691.2005.01235.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of Burkholderia pseudomallei in blood culture supernatants by a coagglutination assay

Abstract: In total, 309 blood culture supernatants were tested for the presence of Burkholderia pseudomallei antigen using an in-house coagglutination test prepared by sensitising Cowan I staphylococcal cells with B. pseudomallei polyclonal antiserum. The coagglutination test gave a sensitivity, specificity, positive predictive value and negative predictive value of 100% in comparison with blood culture. A subset of 102 supernatants was also tested for B. pseudomallei antigen using a monoclonal antibody-based latex aggl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Similar results are shown in a study from Vellore using in-house co-agglutination test and latex agglutination test [32]. In Thailand, the results of rapid immunofluorescence (IF) test and those of an existing IF method were prospectively compared with the culture of various clinical specimens from patients with suspected melioidosis.…”
Section: Rapid Detection Methodssupporting
confidence: 58%
“…Similar results are shown in a study from Vellore using in-house co-agglutination test and latex agglutination test [32]. In Thailand, the results of rapid immunofluorescence (IF) test and those of an existing IF method were prospectively compared with the culture of various clinical specimens from patients with suspected melioidosis.…”
Section: Rapid Detection Methodssupporting
confidence: 58%
“…But all these require expensive devices or complicated protocols [9] thus, are not suitable under routine laboratory conditions. CAT being an inexpensive, simple, sensitive and rapid test had been used for the diagnosis of various diseases [11,15]. Therefore, in the present study, an attempt was made to develop CAT as a sensitive, specific and easy-to-use technique for the rapid identification of bacteria having potential to produce anthrax.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we reported that detection of anthrax toxin by latex agglutination test (LAT) can be an effective technique for the diagnosis of anthrax as well as for the specific identification of cultures of organisms causing anthrax [10]. However, coagglutination test (CAT) is reported to be more sensitive, cheaper and simpler test [11]. Therefore, the present study was planned to evaluate whether CAT can serve as a surrogate for the specific identification of bacteria causing anthrax.…”
Section: Introductionmentioning
confidence: 96%
“…Appropriate biochemicals were also set up [7]. The plates showed growth of non-haemolytic grey colonies at 24 h on sheep blood agar, which turned hazy β-haemolytic by 48 h. On MacConkey agar fine pale colonies formed at 24 h, and the colonies turned pink (lactose fermenting) by 48 h. The colonies were oxidase-positive and showed a 4 + reaction on agglutination with B. pseudomallei -specific antiserum raised in rabbits [8]. The preliminary screening media and other biochemicals confirmed the organism to be B. pseudomallei .…”
Section: Methodsmentioning
confidence: 99%